2006
DOI: 10.1142/s0192415x06004132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Safflower Seed Oil in Osteoporosis Induced-Ovariectomized Rats

Abstract: The effects of Korean Safflower (Carthamus tinctorius L) seed oil (SSO) on osteoporosis induced-ovariectomized rats were investigated. A total of 90 female Sprague-Dawley rats, 4-month-old, weighing 200-230 g were randomly assigned into 3 groups (30 animals/group). The animals in group I were sham operated and those of group II and III were ovariectomized (Ovx). After eight weeks, the animals of group I and II received solvent vehicle daily, whereas those of group III were administered SSO orally (1 ml/kg) dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Our study has shown that the levels of Ca 2+ , P and Mg 2+ are not changed, which is typical of the initial phase of osteoporosis, during which no signi cant loss of bone mineral density due to active bone remodeling and a compensatory increased osteoblast activity is seen [22,23]. Weight gain in animals in the G2 proves that lack of estrogens due to OVX leads to obesity [24,25].…”
Section: Discussionsupporting
confidence: 50%
“…Our study has shown that the levels of Ca 2+ , P and Mg 2+ are not changed, which is typical of the initial phase of osteoporosis, during which no signi cant loss of bone mineral density due to active bone remodeling and a compensatory increased osteoblast activity is seen [22,23]. Weight gain in animals in the G2 proves that lack of estrogens due to OVX leads to obesity [24,25].…”
Section: Discussionsupporting
confidence: 50%
“…Recently, several results suggested that the safflower seeds have possible roles in the improvement of osteoporosis induced-ovariectomized rats. The safflower seeds have a protecting effect on bone loss caused by estrogen deficiency (Alam et al, 2006;Hong et al, 2002). Therefore, the beneficial effect of safflower seeds has been suggested to be mediated, at least Fig.…”
Section: Discussionmentioning
confidence: 99%
“…24,25) Safflower seeds are commonly used as a natural remedy to treat bone fractures in traditional Korean medicine, and have recently been used in regenerative applications. 26,27) Other data on safflower seeds include application to the treatment of periodontal 1-wall intrabony defects, 28) and in the prevention of bone resorption caused by estrogen deficiency. 8) Angelica sinensis has effects on osteoblast proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%